2023
DOI: 10.3390/biomimetics8020228
|View full text |Cite
|
Sign up to set email alerts
|

Chitosan Cryogels Cross-Linked with 1,1,3-Triglycidyloxypropane: Mechanical Properties and Cytotoxicity for Cancer Cell 3D Cultures

Yuliya Privar,
Andrey Boroda,
Alexandr Pestov
et al.

Abstract: Here, we have presented a new method of 1,1,3-triglycidyloxypropane (TGP) synthesis and investigated how cross-linker branching affects mechanical properties and cytotoxicity of chitosan scaffolds in comparison with those cross-linked using diglycidyl ethers of 1,4-butandiol (BDDGE) and poly(ethylene glycol) (PEGDGE). We have demonstrated that TGP is an efficient cross-linker for chitosan at a subzero temperature at TGP:chitosan molar ratios from 1:1 to 1:20. Although the elasticity of chitosan scaffolds incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…It was stated in previous sections that in our study (table 3), mucilage alone could not exhibit a mechanically stable structure. In addition, previous studies have reported that CS has low mechanical strength and degrades rapidly, so its use in biomedical applications is limited [56][57][58]. However, PVA, which has high mechanical strength to the structure, improved the mechanical properties of cryogels as expected.…”
Section: Discussionmentioning
confidence: 79%
“…It was stated in previous sections that in our study (table 3), mucilage alone could not exhibit a mechanically stable structure. In addition, previous studies have reported that CS has low mechanical strength and degrades rapidly, so its use in biomedical applications is limited [56][57][58]. However, PVA, which has high mechanical strength to the structure, improved the mechanical properties of cryogels as expected.…”
Section: Discussionmentioning
confidence: 79%